(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
This study examines the role of customer satisfaction in mediating the relationship between brand image and service quality on the intention to repurchase Olive Fried Chicken. This research is quantitative research. The data obtained in this study were obtained through random sampling data collection methods. The sample in this study was 100 respondents. Statistical analysis in this study used Structural Equation Modeling (SEM) with data analysis method using Partial Least Square (PLS) approach. The results of this study, brand image, and service quality have a positive and significant effect on customer satisfaction; customer satisfaction has a positive and significant impact on repurchase intentions, brand image has a positive and significant impact on repurchase intentions, while service quality has no significant impact on purchase intentions Olive Fried Chicken. Customer satisfaction can mediate the relationship between brand image and repurchase intention and mediate the relationship between service quality and repurchase intention. Penelitian ini bertujuan untuk mengkaji kepuasan pelanggan dalam memediasi hubungan citra merek dan kualitas pelayanan terhadap niat beli ulang Olive Fried Chicken.Penelitian ini merupakan penelitian Kuantitatif. Data yang diperoleh dalam penelitian ini diperoleh melalui metode pengumpulan data random sampling. Sampel dalam penelitian ini sebanyak 100 responden. Analisis statistik dalam penelitian ini menggunakan Structural Equation Modeling (SEM) dengan metode analisis data menggunakan pendekatan Partial Least Square (PLS). Hasil dari penelitian ini, citra merek dan kualitas pelayanan berpengaruh positif dan signifikan terhadap kepuasan pelanggan, kepuasan pelanggan berpengaruh positif dan signifikan terhadap niat beli ulang, citra merek berpengaruh positif dan signifikan terhadap niat beli ulang, sedangkan kualitas pelayanan tidak berpengaruh signifikan terhadap niat beli Olive Fried Chicken ulang.Kepuasan pelanggan mampu memediasi hubungan antara citra merek dengan niat beli ulang dan memediasi hubungan antara kualitas pelayanan dengan niat beli ulang.